FROM LONELINESS TO COOPERATION: COPING STRATEGIES OF INTENSIVE CARE NURSING WORKERS - Estefânia da Silva Oliveira; Alexa Pupiara Flores Coelho Centenaro; Cledir Tânia França Garcia; Cíntia Maria Lovato Flores; Gianfábio Pimentel Franco; Júlia Glowacki (Universidade Federal do Paraná, 2022)
Objective: to know the coping strategies developed by intensive care unit nurse practioners to maintain mental health. Method: qualitative descriptive study, with nursing workers from three Intensive Care Centers in a southern state of Brazil. Data collected between June 2019 and July 2021 through semi-structured interviews and submitted to thematic content analysis. Results: individual coping strategies based on situations that generate suffering were unveiled. The loneliness of work was evidenced because of the mismatches between the therapeutic spaces offered by the institution and the demands of the workers. Finally, the possibility of re-signifying loneliness in cooperation through collective strategies was identified as a path to face suffering at work and as a protective factor of greater effectiveness.  Conclusion: collective coping actions and activities that strengthen the union and cooperation of intensive care nursing teams can be promoted.